Human-Nature Relationship in Heathy Landscape with Dormouse: Greg Gerrard's Ecocritical Approach - Irma Rahmawati; Rochmah Rochmah (Dinasti International Journal of Education Management And Social Science, 2024)
This study seeks the intricate relationship between humans and nature in Sylvia Townsend Warner's short story "Heathy Landscape with Dormouse," applying Greg Gerrard's ecocritical framework to underscore themes of environmental sustainability. The objective is to analyze how Warner's portrayal of rural life and nature underscores the importance of ecological balance and sustainable practices. Through the ecocritical lens, the study examines character interactions with their environment and the symbolic meanings within the narrative. The findings reveal that the story embodies environmental values, with characters like Mrs. Leslie, Belinda, and Leo demonstrating respect for nature and a reliance on natural resources. Symbols such as owls highlight the uniqueness of nature and the necessity for environmental sustainability. Additionally, the study draws connections between the story’s ecological themes and contemporary environmental imperatives, emphasizing the importance of nature, ecological balance, and sustainability. The moral message of the story about protecting ecosystems conveys profound insights into the natural world and humanity's role within it, highlighting the significance of environmental awareness and sustainable practices in achieving ecological balance. This research enhances the understanding of the human-nature relationship in literature and underscores the crucial role of ecological awareness and sustainable practices.